The Politics of Electric Vehicle Subsidies in Indonesia: Actors, Agenda, and Issues - Maulana, Anisyahirah Kalyana Putri; Kurniawan, Yudha (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
In light of the worldwide determination to address the consequences of climate change, the Indonesian government has established a goal of achieving carbon neutrality by the year 2060. The transportation sector in Indonesia is a significant source of carbon emissions due to its extensive reliance on fossil fuel consumption. In response to this challenge, the Indonesian government has implemented measures to expedite the motor vehicle electrification program by introducing a subsidy policy aimed at facilitating the public’s acquisition of electric vehicles. The formulation of this strategy initiated a sequence of discussions within the public domain. In order to gain a comprehensive understanding of the many actors involved and the process of discourse formation within the discussion, this study has undertaken the collection of 198 stakeholder statements as presented in articles published by national mass media outlets throughout the period spanning from January 2023 to June 2023. This statement mapped with the Discourse Coalition Framework (DCF) theory to find the network of discourse and ideas as the data that was subsequently subjected to analysis utilizing the Discourse Network Analysis. The findings of this study indicate that the discourse surrounding the subsidy program for electric vehicles gave rise to actor network groups that advocated investment and concerns related to environmental sustainability. The author examines the limitations to the interconnections between theoretical frameworks empirical evidence in shaping the discourse surrounding the dynamics of network politics in relation to electric vehicle subsidies in Indonesia.